PIM Kinase Inhibitor AZD1208 for Treatment of MYC-Driven Prostate Cancer - Kirschner, Austin N. (J Natl Cancer Inst, 2014)
BACKGROUND: PIM1 kinase is coexpressed with c-MYC in human prostate cancers (PCs) and dramatically enhances c-MYC-induced tumorigenicity. Here we examine the effects of a novel oral PIM inhibitor, AZD1208, on prostate tumorigenesis and recurrence. METHODS: A mouse c-MYC/Pim1-transduced tissue recombination PC model, Myc-CaP allografts, and human PC xenografts were treated with AZD1208 (n = 5–11 per group). Androgen-sensitive and castrate-resistant prostate cancer (CRPC) models were studied as well as the effects of hypoxia and radiation. RNA sequencing was used to analyze drug-induced gene expression changes. Results were analyzed with χ(2) test. Student’s t test and nonparametric Mann-Whitney rank sum U Test. All statistical tests were two-sided. RESULTS: AZD1208 inhibited tumorigenesis in tissue recombinants, Myc-CaP, and human PC xenograft models. PIM inhibition decreased c-MYC/Pim1 graft growth by 54.3±39% (P < .001), decreased cellular proliferation by 46±14% (P = .016), and increased apoptosis by 326±170% (P = .039). AZD1208 suppressed multiple protumorigenic pathways, including the MYC gene program. However, it also downregulated the p53 pathway. Hypoxia and radiation induced PIM1 in prostate cancer cells, and AZD1208 functioned as a radiation sensitizer. Recurrent tumors postcastration responded transiently to either AZD1208 or radiation treatment, and combination treatment resulted in more sustained inhibition of tumor growth. Cell lines established from recurrent, AZD1208-resistant tumors again revealed downregulation of the p53 pathway. Irradiated AZD1208-treated tumors robustly upregulated p53, providing a possible mechanistic explanation for the effectiveness of combination therapy. Finally, an AZD1208-resistant gene signature was found to be associated with biochemical recurrence in PC patients. CONCLUSIONS: PIM inhibition is a potential treatment for MYC-driven prostate cancers including CRPC, and its effectiveness may be enhanced by activators of the p53 pathway, such as radiation.